The Existence of Customary Law in Preserving Culture as a Tourism Attraction: A study from Senaru Village, North Lombok, West Nusa Tenggara - Komang Mahawira (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
This research addresses customary law's role in maintaining culture as a cultural tourism attraction in Senaru village. This study used a qualitative approach by interviewing three key informants responsible for implementing customary law in Senaru Village. This study concludes that customary law plays a significant role in maintaining the existence of culture as a cultural tourism attraction. The customary law of Senaru Village has solid legal principles, substance, structure, and sanctions and is still maintained by the Senaru Village community. This study hopes to encourage the peoples to continue preserving and obeying the customary law in their village by respecting the existence of the Raden, Toak Lokaq, Pembekel, and Kyai, and adhering to the norms of customary law that apply in order to maintain social harmony. Moreover, it is advised for domestic and foreign tourists to continue respecting and upholding the applicable customary law by not violating any prohibitions in Senaru village. Lastly, the local government is urged to continue recognizing and protecting the customary law community to ensure sustainability.